3x+2y-5=ax+by+1

Simple and best practice solution for 3x+2y-5=ax+by+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2y-5=ax+by+1 equation:


Simplifying
3x + 2y + -5 = ax + by + 1

Reorder the terms:
-5 + 3x + 2y = ax + by + 1

Reorder the terms:
-5 + 3x + 2y = 1 + ax + by

Solving
-5 + 3x + 2y = 1 + ax + by

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1ax' to each side of the equation.
-5 + 3x + -1ax + 2y = 1 + ax + -1ax + by

Reorder the terms:
-5 + -1ax + 3x + 2y = 1 + ax + -1ax + by

Combine like terms: ax + -1ax = 0
-5 + -1ax + 3x + 2y = 1 + 0 + by
-5 + -1ax + 3x + 2y = 1 + by

Add '5' to each side of the equation.
-5 + -1ax + 3x + 5 + 2y = 1 + 5 + by

Reorder the terms:
-5 + 5 + -1ax + 3x + 2y = 1 + 5 + by

Combine like terms: -5 + 5 = 0
0 + -1ax + 3x + 2y = 1 + 5 + by
-1ax + 3x + 2y = 1 + 5 + by

Combine like terms: 1 + 5 = 6
-1ax + 3x + 2y = 6 + by

Add '-2y' to each side of the equation.
-1ax + 3x + 2y + -2y = 6 + by + -2y

Combine like terms: 2y + -2y = 0
-1ax + 3x + 0 = 6 + by + -2y
-1ax + 3x = 6 + by + -2y

Reorder the terms:
-6 + -1ax + -1by + 3x + 2y = 6 + by + -2y + -6 + -1by + 2y

Reorder the terms:
-6 + -1ax + -1by + 3x + 2y = 6 + -6 + by + -1by + -2y + 2y

Combine like terms: 6 + -6 = 0
-6 + -1ax + -1by + 3x + 2y = 0 + by + -1by + -2y + 2y
-6 + -1ax + -1by + 3x + 2y = by + -1by + -2y + 2y

Combine like terms: by + -1by = 0
-6 + -1ax + -1by + 3x + 2y = 0 + -2y + 2y
-6 + -1ax + -1by + 3x + 2y = -2y + 2y

Combine like terms: -2y + 2y = 0
-6 + -1ax + -1by + 3x + 2y = 0

The solution to this equation could not be determined.

See similar equations:

| -144=-3-3(5+6k) | | 84x^2-238x-196=0 | | 7n+12=32 | | (25/8)(2/5) | | 24-x/3=6 | | 5(3x-5)=6(x-2)-19 | | (4n/7)+(3n/2)=-3 | | (12n+20)-4-8n=6-2n | | 3x^2+40x+112=0 | | 3/4x-1/4x=-11 | | 25/8*2/5 | | -13+5x=12 | | 1/(14-3x)=2/(5x+4) | | 0.7t=0.3+0.9t | | 2p+5r=a | | 3(5-2r)-2(-3r+1)= | | 10x-(4x-8)=50 | | 4(5-4k)=-60 | | 8-34= | | 4+6/x | | 14=5x+2 | | -3(x-8)=18 | | (6x+20)+(2x+4)=164 | | (3x+2)/4=16-2x | | Y+3/r=r^2 | | 3,823=5/100 | | -2(7y-5)=-14y-23 | | -18-11r=2b | | 1/4+1/5+1/2+150 | | 2(3z+1)-8=48 | | 8-5(z+2)=-2(5z-2)-2 | | 2x+11+x+7=18 |

Equations solver categories